Evaluation of Gas Lift Deepening Design Using a Retrofit Gas Lift System to Increase Well Production in an Offshore Field: Case Study of Well S-7 - Suhartanto, Surya Arif Wibowo; Budi, Iwan Setya; Damargalih, Yono (UIR PRESS, 2024)
S-7 well is a horizontal well in the NDF Field that produces hydrocarbons from carbonate formation for over seven years using gas lift. Over time, S-7 well has experienced a significant decline in production due to reservoir pressure along with an increase in water cut. To address this issue, a well intervention was conducted to deepen the injection point by installing Retrofit Gas Lift technology, aiming to enhance the well's production to an optimal level. This research focuses on evaluating the application of Gas Lift Deepening using Retrofit Gas Lift (RGL) in Well S-7 through well modeling methods with PROSPER software and providing recommendations for an optimal Gas Lift Deepening design. The study analyzes well modeling for Well S-7 before and after RGL installation, validated using well test data to compare production performance in both scenarios. The evaluation proceeds by identifying the parameters that influence the effectiveness of the Retrofit Gas Lift (RGL), followed by designing an optimized RGL system to enhance production performance. Based on the research, the installation of the Retrofit Gas Lift (RGL) in Well S-7 resulted in an increase in the production rate of 78.58 STB/d. Sensitivity testing identified key factors influencing the production rate, including reservoir pressure, top node pressure, gas injection rate, coil tubing size, and coil tubing length. Design optimization by adjusting the top node pressure to 130 psi, coiled tubing length to 2000 ft, coiled tubing size to 1.75 in, and gas lift injection rate to 1 MMSCFD resulted in an increased flow rate of 220.86 STB/d and a drawdown of 751.77 psi.